Reparations and war : finding balance in repairing the past - Moffett, Luke (Oxford University Press, 2023)
For thousands of years, reparations have been used to alleviate the devastating consequences of war. More recently, human rights law has established that victims have a right to reparations. Yet, in the face of conflicts that last for decades with millions of victims, how feasible it is to deliver reparations? And what are the obstacles?